Study of the role of Mce3R on the transcription of mce genes of Mycobacterium tuberculosis - Santangelo, María P (BioMed Central, 2008)
BACKGROUND: mce3 is one of the four virulence-related mce operons of Mycobacterium tuberculosis. In a previous work we showed that the overexpression of Mce3R in Mycobacterium smegmatis and M. tuberculosis abolishes the expression of lacZ fused to the mce3 promoter, indicating that Mce3R represses mce3 transcription. RESULTS: We obtained a knockout mutant strain of M. tuberculosis H37Rv by inserting a hygromycin cassette into the mce3R gene. The mutation results in a significant increase in the expression of mce3 genes either in vitro or in a murine cell macrophages line as it was determined using promoter-lacZ fusions in M. tuberculosis. The abundance of mce1, mce2 and mce4 mRNAs was not affected by this mutation as it was demonstrated by quantitative RT-PCR. The mce3R promoter activity in the presence of Mce3R was significantly reduced compared with that in the absence of the regulator, during the in vitro culture of M. tuberculosis. CONCLUSION: Mce3R repress the transcription of mce3 operon and self regulates its own expression but does not affect the transcription of mce1, mce2 and mce4 operons of M. tuberculosis.